Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

High carbon burial fluxes in lakes do not equate to stable carbon sinks: Evidence from typical large river-connected lake systems - Zheng Huang; Shilan Wang; Zhongwu Li; Fengwei Ran; Ming Chen; Xiaodong Nie; Xinyu Ling; Chengyu Zhong (Water Research, 2026)

Pre-transport dietary chitosan improves the physiological robustness of juvenile largemouth bass (Micropterus salmoides) by modulating antioxidant and inflammatory responses - Hong-Zheng Zhao; Yu-Lin Chang; Chang Wang; Yu-Yun He; Yi-Ran Zhao; Yi-Chen Dong; Xu-Xiong Huang; Guo-Fang Zhong (Fish & Shellfish Immunology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Self-driven Co-Cu@Pt MOF Micro/nanomotors composite membrane for overcoming diffusion-limited mass transfer in efficient removal of organic micropollutants - Liyuan Fu; Xia Zheng; Bin Ran; Guangyong Zeng; Xi Chen; Yuan Xiang; Jianquan Luo (Chemical Engineering Journal, 2026)

Comparative analysis on antioxidant capacity, immunity and mortality changes of pikeperch (Sander lucioperca) in response to mono-infection or co-infection with Nocardia seriolae and Aeromonas salmonicida - Junchen Li; Jing Wang; Zhipeng Sun; Ran Zhao; Xianhu Zheng; Shaowu Li; Cuiyun Lu; Di Wang (Aquaculture, 2026)

Combined regulation of CO2 and nutrients on carbon fixation and emission of Microcystis aeruginosa: physiological and transcriptomic insights - Jiao Ran; Guo Li; Lijing Wang; Binghui Zheng; Ensheng Zhu; Rong Xiang; Shanyuan Xue; Zheng Zheng (Water Research, 2026)

Groundwater dynamics induced by tunneling and reservoir filling at the site of Kala hydropower project - Ao Liu; Ying-Feng Zhang; Yi-Feng Chen; Ran Hu; Zhibing Yang; Jia-Qing Zhou; Hai-Sheng Zheng; Heng-Yi Gan; Bin Chen; En-Ming Zhang (Tunnelling and Underground Space Technology, 2026)

Combined lead exposure and high-copper intake exacerbates synaptic loss via METTL3-mediated m6A methylation in mice - Ran Li; Shuangshuang Tan; Di Wu; Huijing Wang; Yuqi Li; Jiayi Xiong; Haojie Tian; Tao Wang; Gang Zheng (Toxicology Letters, 2026)

A room temperature activatable highly-conductive liquid metal ink and its flexible electrohydrodynamic printing - Xu Chen; Yiwen Feng; Kaiwen Chen; Zhenya Wang; Gengyuan Li; Chang Liu; Shulei Zheng; Chumeng Zhang; Zefei Li; Xiangji Chen; Xiaopeng Zhang; Ran Zhang; et al. (Chemical Engineering Journal, 2026)

Traceable method for differential code bias estimation in PPP one-way timing - Fu Zheng; Conghan Wang; Xiaopeng Gong; Cheng Yang; Dong Zhang; Yu Xue; Ran Yao; Yuzhuo Wang; Chuang Shi (GPS Solutions, 2026)

A combined nutrient supply and spectral shift strategy for enhanced biomass, lipid, and fucoxanthin co-production in Phaeodactylum tricornutum - Qiufeng Song; Ran Xu; Jingwei Nan; Lei Zheng; Luyun Cai; Changhong Liu (Algal Research, 2026)

Cross-scale mapping of Leaf Nitrogen Content in arid desert shrubs by integrating UAV and satellite data under sparse sample conditions - Chenglong Xin; Jie Bai; Hongwei Zheng; Ran Liu; Yongbo Zhao; Duoyuan Shi; Jinfeng He; Yong Zhu (International Journal of Remote Sensing, 2026)

Mapping mollic epipedon thickness via ground-penetrating radar based on the combined method of Variational Mode Decomposition and Average Envelope Amplitude - Haipeng Lu; Xiangming Zhu; Wenjuan Zheng; Bin Zhang; Tianhao Wang; Yu Zhang; Meiling Fu; Enhua Ran (Soil and Tillage Research, 2026)

Geodynamics of the Longriba fault zone on the eastern margin of the Tibetan Plateau: Insights from sedimentary Basin and low-temperature thermochronology - Yin Li; Shugen Liu; Zhiwu Li; Jinxi Li; Bo Ran; Kui Tong; Jie Hu; Chaoqun Yang; Zhiyuan Zheng; Bing Li; Tianrui Wang (Journal of Asian Earth Sciences, 2026)

PAN4, an AI-designed host-directed immunomodulatory peptide, promotes PGRP-SC1a-associated intestinal immune homeostasis in Drosophila melanogaster - Yanying Sun; Yanan Wei; Wenjie Jia; Xinyue Zhou; Ran Dong; Zekun Wu; Hongyu Miao; ZhenZhi Li; Zheng Chen; Chaoran Liu; Weijie Yuan; Ying Hu; et al. (Insect Biochemistry and Molecular Biology, 2026)

The interactive role of concentrated freshly squeezed tea juice supplementation on structural and in vitro digestibility of dried Nigari tofu - Mei-Xuan He; Ibrahim Khalifa; Xiao-Min Zeng; Jian Zheng; Wen Zhang; Zhu-Cheng Su; Noman Walayat; Ran Wei (Food Chemistry, 2026)

NIR-elicited hydrogel contraction modulates rheological dynamics for spatiotemporally controlled metallo-drug release to potentiate cuproptosis-driven immunotherapy - Wenpei Luo; Lingyun He; Weiwei Liu; Xin Gao; Long Cheng; Min Zheng; Jianli Ren; Haitao Ran; Xun Guo; Lu Yang (Chemical Engineering Journal, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Viral community dynamics and functional succession in advanced drinking water treatment processes - Yuhong Zheng; Chunjing Chen; Dan Guan; Yang Huang; Lilin Xiong; Ran Liu (Archives of Microbiology, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Seismic centrifuge tests of embankments on saturated soft clay improved with concrete columns - Jihui Zhao; Tianqi Bian; Haizuo Zhou; Chenhao Xia; Gang Zheng; Ran Yuan (Transportation Geotechnics, 2026)

Dynamic centrifuge tests for evaluating the effects of caps on the seismic responses of column-supported embankments on saturated soft clay - Jihui Zhao; Chaoge Tong; Chenhao Xia; Qianhui Guo; Haizuo Zhou; Tianqi Bian; Gang Zheng; Ran Yuan (Transportation Geotechnics, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A self-oxygenating, ROS-responsive nanoplatform potentiates sonodynamic-immunotherapy via STING activation in pancreatic cancer - Qiyi Feng; Xiao Wen; Chunxiu Xiao; Zhifan Wang; Qingqing Ran; Ling Wang; Sisi Yi; Xiuli Zheng; Zhaoyan Chen; Fangyuan Tian; Junjie Xiong; Haibo Wang; et al. (Chemical Engineering Journal, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Novel photoelectron-driven nitrate reduction in anammox granules using photosensitive semiconductor iron mineral for wastewater treatment - Xue Wang; Tao Xue; Jian Li; Caiyun Zhang; Guizhen Hao; Yuzi Xing; Ran Tao; Lin Guo; Haozhe Zhang; Shu Chai; Lei Zheng (Water Research, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Electrochemically triggered self-reconstruction of CuPd alloys for high-efficiency furfural electrohydrogenation - Yunfei Ran; Guanhua Cheng; Kuibo Yin; Jiameng Sun; Anqi Zheng; Xiangyu Fei; Yalong Liu; Zhenhan Li; Tianyi Kou; Zhonghua Zhang (Chemical Engineering Journal, 2026)

Multi-objective optimization of urban residential morphology in cold regions based on energy consumption reduction and solar radiation utilization potential enhancement - Peng Cui; Zixin Guo; Yang Song; Yewei Zheng; Ran Ji; Jiaqi Lu (Sustainable Cities and Society, 2026)

New grylloblattid insect from the Lower Triassic Kayitou Formation of Yunnan Province, Southwest China - Shi-Xue Hu; Jin-Yuan Huang; Qi-Yue Zhang; Chang-Yong Zhou; Wen Wen; Xiao Min; Da-Ran Zheng; Qian-Qi Zhang (Palaeoworld, 2026)

Source apportionment and health risk prioritization of groundwater contamination in a coal-mining area: An integrated SOM-PMF-Monte Carlo framework - Zheng Yin; Shiqi Zhang; Xiao Fu; Ran Sun; Ran Lv; Meng Yuan; Ziyuan Gao; Gang Wu (Journal of Environmental Management, 2026)

Expression and functional analysis of glutathione S-transferase gene GmGST2a different tissues of from Galleria mellonella larvae - Yangyang Liu; Ziliang Zheng; Xuyu Ran; Jiajuan Shen; Shengfeng Liu; Yingying Li; Guoyong Li (Journal of Asia-Pacific Entomology, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Life cycle carbon footprint analysis of power batteries considering changes in electricity mix - Ning Yu; Lan Xia; Zhiyi Ran; Hao Zheng (The International Journal of Life Cycle Assessment, 2026)

High-Frequency Signal Recovery via the Constraint of Reflection Structure in f-x Domain - Chong Sun; Nan-ying Lan; Duo-ming Zheng; Hao-nan Tian; Shi-kai Jian; Lang Yang; Zhi-fang Ran; Rui-dong Liu (Applied Geophysics, 2026)

Toxoplasma GRA72 is Involved in Membrane-Associated Functions and Metabolic Homeostasis Revealed by Transcriptomic Analysis - Xin-Sheng Lu; Xing Tian; Jing Li; Chen-Ran Tian; Xing-Quan Zhu; Xiao-Nan Zheng (Acta Parasitologica, 2026)

The effect of mangrove restoration on sediment carbon stock in early decade: A comparative evidence from natural and restored mangroves - Cuiping Zhang; Ran Yan; Huamei Huang; Zhaoyong Zheng; Xianhui Yang; Jianxiang Feng; Zilin Chen (Regional Studies in Marine Science, 2026)

Soil water vapor adsorption and condensation governed by groundwater depth and vadose zone lithology in arid and semi-arid regions - Ran Li; Haibo Feng; Yanhong Xue; Jianwei Zhou; Lei Fang; Danhui Su; Xiaoming Zheng; Siqi Tan; Huyuan Zheng; Yongxiang Ma (Journal of Hydrology, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Compartment-specific assembly and functional characterization of the bacterial microbiome in a Pinus radiata- Lactarius deliciosus plantation system - Jing Yuan; Yanliang Wang; Xueqiong Zhang; Zhuyue Yan; Ran Wang; Chengmo Yang; Xinhua He; Jesús Pérez-Moreno; Fuqiang Yu; Yi Zheng (Applied Soil Ecology, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The transcriptional regulatory module MdERF2-MdSCR11 promotes ABA-mediated apple fruit ripening through synergistic repression of MdABA4-2 - Miaomiao Wang; Qizhe Li; Hao Wang; Nan Jiang; Jiale Wang; Xiaotong Hu; Yu Liu; Tuanhui Bai; Jian Jiao; JiangLi Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2026)

Pollution characteristics of Litopenaeus vannamei greenhouse effluents and purification performance of a combined flocculation–ecological floating bed system - Shanyuan Xue; Guo Li; Ensheng Zhu; Weizhen Zhang; Jiao Ran; Zhe Li; Yu Zhao; Jingru Hu; Jing Dong; Yingxue Yi; Dan Zhou; Qiang He; et al. (Journal of Environmental Chemical Engineering, 2026)

Pressure-driven flavor formation in rapeseed oil: an integrated multi-omics approach - Yini Yang; Chang Zheng; Ran Zhao; Ya Xu; Lanhang Yao; Wenlin Li; Changsheng Liu; Chuyun Wan; Qi Zhou (Food Chemistry, 2026)

Catalyzed in-situ amination of support layer for thermally stable forward osmosis membranes in industrial dyeing wastewater concentration - Qin Zheng; Meng-ran Xu; Dai-feng Song; Wen-shi Liu; Hao-Ran Zuo; Ming Duan (Desalination, 2026)

Porous MXene nanoplatform with ultrahigh drug loading for synergistic photothermal/photodynamic therapy and drug resistance reversal in osteosarcoma - Zhen Song; Ran-Ran Zhang; Zi-Chao Yan; Jie Wang; Youchang Liu; Chang-Qing Jiang; Meng Qiu; Bing-Xin Zheng; Bin Yue (Chemical Engineering Journal, 2026)

Water-resistant, flexible and transparent cellulose nanofibril film for exceptional oxygen-barrier performance under high humidity - Zhaodi Zheng; Ran Wu; Qi Li; Xiaowei Wu; Dan Qiu; Zhanghui Wang; Hongzhi Liu (Carbohydrate Polymers, 2026)

Revegetation mechanisms and influence factor in alpine mining areas: a case study of the Muli mining area, Qinghai-Tibet Plateau - Kaixin Zhang; Qingqiu Hou; Haibo Feng; Linxue Ju; Jianwei Zhou; Jun Li; Ruimin Xiong; Yi Zhu; Xiaoming Zheng; Ran Li; Chunguang Wang (Plant and Soil, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Effects of industrial solid wastes on the rheological behavior and electrical resistivity-acoustic emission responses of cement-based grouted bodies under loading - Xinchao Zheng; Qiang Sun; Fang Liu; Yuhang Li; Boxing Yang; Ran Tang (Journal of Environmental Management, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Interfacial engineering of polyolefin separators via caffeic acid-titanium coating for high-efficiency lithium dendrite suppression - Zi-Yin Chen; Zhen Luo; Cui-Ran Gong; Yang-Qing Zheng; Ying Xu (Chemical Engineering Journal, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Enhancing ADMET property predictions using cross-aligned multimodal attention mechanisms - Xinkang Li; Yilin Ye; Ran Xu; Fangfang Jiao; Ziping Hu; Henry H. Y. Tong; Liangzhen Zheng; Jingjing Guo (Molecular Diversity, 2026)

Spatiotemporal patterns and driving factors of nitrogen concentrations in Daya bay via remote sensing - Jingjing Huang; Difeng Wang; Lihua Ran; Xianqiang He; Zhuoqi Zheng; Qing Zhang; Aifen Zhong; Fang Gong; Qiankun Zhu (Marine Pollution Bulletin, 2026)

Research on the influencing factors and prediction model of carbon storage of urban forest in Harbin, China - Peng Cui; Yewei Zheng; Lei Wang; Jiajie Tian; Ran Ji; Zixin Guo (Urban Forestry & Urban Greening, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Optimizing partial nitrification-anammox in a membrane aerated moving bed biofilm reactor for mainstream nitrogen removal - Xiao Ran; Yulong Yang; Zhihong Zheng; Hongyu Wang; Xingyu Zheng; Xiling Peng; Jie Yao; Minhua Wei; Shuang Zhang; Jin Xu (Journal of Environmental Chemical Engineering, 2026)

Removal of Mg2+ and Al3+ from high-concentration wet-process phosphoric acid by NH4MgAlF6 complexation-precipitation - Ran Zhu; Zili Wang; Yangyang Luo; E. Yang; Shisong Yang; Qian Lin; Hongyan Pan; Zheng Chen (Journal of Environmental Chemical Engineering, 2026)

Simulation study on burning flux of biodiesel/NH3/CO2/H2O flames with consideration of radiation reabsorption - Hao Liu; Shu Zheng; Tipeng Wang; Ran Sui; Qiang Lu (Fuel, 2026)

A LLM-based agent for the construction of typhoon knowledge graphs - Yi Huang; Yongqi Xia; Ran Tao; Donglai Jiao; Xiangqiang Min; Jieying Zheng; Yuting Jiang; Wenjun Wu; Peijun Du (Environmental Modelling & Software, 2026)

Exploration of the pathway and mechanism of phycocyanin accumulation: A review - Xiaoxuan Zhou; Zhengdong Wan; Ran Gao; Jianxiong Hao; Wei Wang; Xuechao Zheng; Dandan Zhao (Bioresource Technology Reports, 2026)

Elevated CO2 has a greater impact on surface soil carbon but warming on subsoil carbon: evidence from SOC accumulation and stability - Yaran Fan; Bingbing Yu; Shaopan Xia; Ziqi Zhu; Lukas Van Zwieten; Yufei Zhong; Aoxue Cai; Ran Wang; Zhaoliang Song; Wei Yang; Yuchuan Fan; Xiaoyu Liu; et al. (Plant and Soil, 2026)

Contrasting effects of long-term nitrogen and phosphorus fertilization on phosphorus availability in soil - Ran Tong; Han Yu; Nianfu Zhu; Yongzhao Miao; Song Chen; Yeshi Zheng; Tonggui Wu; G. Geoff Wang; Yakov Kuzyakov (Soil Ecology Letters, 2026)

Forecasting ecosystem service values in South China’s fragile mountain regions: a multi-scenario analysis with adaptive land use valuation - Zhaoyang Liao; De Yu; Penglai Ran; Defu Zheng; Guiduo Shang; Jie Tan (Journal of Mountain Science, 2026)

An optimal method for GNSS water vapor tomography based on parameter adaptation - Fei Yang; Ruixian Hao; Haoyu Wang; Lei Wang; Zhicai Li; Junxi Zheng; Yingying Wang; Ran Chen (GPS Solutions, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Integrated transcriptomic and physiological analysis highlights the candidate genes regulating enzymatic browning, antioxidant capacity, and lipid metabolism in pomegranate aril browning - Yawen Shen; Sen Wang; Ran Wan; Jian Jiao; Yujie Zhao; Liu Cong; Kunxi Zhang; Pengbo Hao; Yu Liu; Wanyu Xu; Miaomiao Wang; Jiangli Shi; et al. (Postharvest Biology and Technology, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Bio-based anhydride crosslinked furan-derived vitrimeric epoxy networks with intrinsic flame retardancy, self-healing capacity and recyclability - Tian-Mo Yang; Hao-Xin Niu; Wen-Jie Zheng; Hao-Ran Jiang; Yuan Hu; Xin Wang (Journal of Cleaner Production, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Tillage effect on soil N uptake and utilization by the changes of chiA and aprA gene under parallel nitrogen application - Linling Ran; Junqiang Wang; Haoyang Wu; Yunyin Xue; Jinglong Wang; Wei Wei; Xinkun Hu; Xiaoqin Qiu; Shuang Yan; Hao Shi; Shaikun Zheng (European Journal of Agronomy, 2026)

Application of explainable machine learning in the study of urban ecological economic resilience - Xiaofeng Ran; Bowen Zhang; Rui Ding; Shuyue Jiang; Jiarui Yuan; Yaoyao Zheng; Changpeng Yang (Ecological Modelling, 2026)

High-Fidelity Morphological and Mineralogical Reconstruction of Chang’E-5 Lunar Regolith Grains - Quan Zheng; Ziwei Tian; Songzheng Yu; Ronghua Pang; Guang Zhang; Guanghui Liu; Yiwei Liu; Yang Li; Xin Liu; Shijing He; Ran Niu; Peng Zhang (Computers and Geotechnics, 2026)

Dual-interface MXene engineering for low-noise perovskite photodetectors in optical communication and health monitoring - Shareen Shafique; Haodong Wang; Yegang Lu; Taimoor Iqbal; Yuheng Wang; Baihui Shen; Ran Zhao; Li Sheng; Cheng Yang; Muhammad Sulaman; Fei Zheng; Ziyang Hu (Chemical Engineering Journal, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Flexible-rigid coupling configuration for advanced energy-sensing integrated microsystems - Chang-Liu He; Yao Tan; Hao Zheng; Cheng Tu; Xin-Ran Zhang; Dong-Ming Fang; Xu Zeng; Xiao-Sheng Zhang (Chemical Engineering Journal, 2026)

Coffee shell as a green reductant for iron recovery from pyrite cinder: synergy of biomass-driven reduction and acid leaching - Xiaojiao Li; Ruiquan Ran; Wei Zeng; Shan Ren; Yibin Wang; Aibin Zhu; Chunli Zheng (Minerals Engineering, 2025)

Reservoirs enhance bacterial diversity but destabilize microbial co-occurrence network compared to natural lakes: A global meta-analysis - Lei Zheng; Yaoxin Zhang; Qiuyang Tan; Xue Wang; Yuzi Xing; Qi Tian; Ran Tao; Haozhe Zhang (Journal of Hydrology, 2025)

The coexistence of Bacillus haynesii and Bacillus tequilensis achieves synchronous algicidal activity and denitrification and enhances the MC-LR degradation of phycosphere microbiota - Yuzi Xing; Lei Zheng; Zixuan Li; Guizhen Hao; Xue Wang; Ran Tao; Qi Tian; Yaoxin Zhang; Haozhe Zhang (Journal of Hazardous Materials, 2025)

Acid and antibiotic stress suppresses soil microbial carbon use efficiency via fungal proliferation: Mechanistic insights from microbial community dynamics - Fengwu Zhou; Xiangmei Zhai; Zongren Dai; Ming Zhou; Ziyi Zhao; Ran Liu; Xinrui Zhang; Shuai Zhang; Zezhen Pan; Wenhui Zhong; Zheng-Shuang Hua; Ming Nie; et al. (Journal of Hazardous Materials, 2025)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

Proteomic, metabolomic and lipidomic profiles provide insights on milk quality differences during heat treatment - Meiqing Chen; Ran Xiao; Shuang Du; Ashikur Rahman; Nan Zheng; Yangdong Zhang; Tianjiao Niu; Jiaqi Wang (Food Chemistry, 2025)

Topology optimization of assembled mechanical metamaterials for large-scale structures - Ran Zheng; Bing Yi; Long Liu; Jia Liu; Xiang Peng; Gil Ho Yoon (Engineering Structures, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Astragaloside IV protects against high altitude hypoxia-induced cardiac injury through the CaSR-NF-kB and EGFR-PI3K-AKT-MDM2 pathways - Xiaowen Li; Ruiqi Cao; Ling Zhang; Jie Chen; Zhen Qin; Danyi Huang; Yazhen Nie; Zheng Duan; Lingling Pu; Zirou Wang; Ran Li; Xinxing Wang; et al. (Apoptosis, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

A highly fractionated origin for the Yanshanian water-rich A-type granite in the Southern Great Xing’an Range, NE China: Insights from zircon and monazite geochemistry - Zi-Yi Wang; Hao Yang; Hao-Ran Wu; Zhi-Chao Zhang; Zheng Ji; Yu Dong; Wen-Chun Ge (Journal of Asian Earth Sciences, 2025)

Bi-modal synergistic hydrogel sensors coupled with machine learning enable gesture parsing and identity recognition - Bihai Yang; Yuwen Li; Kai Zheng; Yan Xiong; Xiaokun Jin; Lixian Zhu; Ran Cai; Bin Hu (Chemical Engineering Journal, 2025)

A comprehensive perspective on intestinal health, physiological status, and growth performance of Larimichthys crocea with different stocking densities in recirculating aquaculture systems - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture International, 2025)

A new flavonostilbene glycoside and four new stilbene derivatives from the roots of Polygonum multiflorum - Shuo-Guo Li; Zheng-Ran Zou; Xiao-Feng Zheng; Yue Sun; Shu-Mei Wang (Natural Product Research, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Turbulence effects and prediction model on particle-bubble collision efficiency - Kaixin Zheng; Xiaokang Yan; Lijun Wang; Jincai Ran; Haijun Zhang (Journal of Environmental Chemical Engineering, 2025)

Advancing nanomaterial adsorbents for water purification: PEG-modified MoS₂ nanoflowers target diclofenac in the aquatic environment - H.M. Solayman; Che-Jung Hsu; Zhe-Ru Zheng; Dhivya Jagadeesan; Azrina Abd Aziz; Kuan Shiong Khoo; How-Ran Chao; Jheng-Jie Jiang (Journal of Environmental Chemical Engineering, 2025)

Study on the synergistic effect of nitrogen fertilizer and Azospirillum brasilense in reducing heavy metal accumulation in pakchoi - Lukuan Huang; Xiaohang Sun; Shihao Zheng; Hezi Bai; Ran Wu; Yaxin Zhu; Shaoting Du (Journal of Environmental Chemical Engineering, 2025)

Nitrogen cycling and ecological impacts mediated by water mass interactions in the Yangtze river estuary and the adjacent east China Sea: insights from nitrogen and oxygen isotopes - Ziying Zhou; Zhi Yang; Bin Wang; Haiyan Jin; Lihua Ran; Zhibing Jiang; Qianna Chen; Feng Zhou; Hao Zheng; Jianfang Chen (Continental Shelf Research, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Mannan oligosaccharides reduce the carbon footprint by decreasing methane emission and nitrogen excretion in Xiangdong black goats - Jing Wang; Ting Liu; Jianfeng Xu; Huihui Liu; Kang Sun; Huiyu Fan; Shengxin Zhu; Hang Ran; Chen Zheng (Animal Feed Science and Technology, 2025)

Effects of exercise intensity on large yellow croaker (Larimichthys crocea): A comprehensive analysis of growth, physiology, muscle fiber structure, and gut health - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Jie Ding; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

Synergistic experimental-numerical investigation of performance optimization and dynamic behavior in perforated electrode electrocoagulation systems for emulsified oil wastewater remediation - Ang Li; Bing Wang; Meng Yao; Zhilin Ran; Zheng Ju; Ting Chen (Process Safety and Environmental Protection, 2025)

CdS-mediated electron dynamics in light-assisted anaerobic digestion: Simultaneous cadmium sequestration and methane enrichment by alkali pretreatment - Baowei Zhang; Xiang Tang; Linrui Zhong; Jiangfu Zheng; Huannian Xiao; Yizhan Deng; Zezhong Ran; Mengqi Wei; Lifang Liu; Changzheng Fan (Journal of Hazardous Materials, 2025)

Enhancing bioavailability and functionality of plant peptides and proteins: A review of novel strategies for food and pharmaceutical applications - Salumu Masuwa Shadrack; Yezhi Wang; Shichao Mi; Ran Lu; Yutong Zhu; Zheng Tang; David Julian McClements; Chongjiang Cao; Xiao Xu; Wenjun Li; Biao Yuan (Food Chemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

CT2 is involved in yield-related traits and cell proliferation of maize - Yong Shi; Ran Xue; Qi Zheng; Zhanyong Guo; Chen Wang; Lanjie Zheng; Yankun Li; Jianping Yang; Weihuan Jin; Jihua Tang; Xu Zheng (Journal of Genetics, 2025)

A novel fenton-like catalyst for efficient degradation of tetracycline: Application of the concept of “treating the wastes with wastes” - Lang Ran; Yajuan Zheng; Xu Zhang; Weidong Xiao; Lingxiao Zhu; Junlan Tang; Yaoguo Wu; Lincheng Zhou (Waste Management, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Air flow field Testing, simulation and Optimization of CO2 air-source heat pump outdoor unit arrays - Li Xiaoyu; Shi Lin; Ma Li; Xu We; Wang Tiansheng; Zheng Siyu; Tian Ran; Yuan Jing; Cui Yujia (Energy and Buildings, 2025)

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

A multi-scale mapping approach of local climate zones: A case study in Hong Kong - Maoping Wang; Ran Wang; Wanlu Ouyang; Zheng Tan (Urban Climate, 2025)

Effects of drying on biofilm-mediated sediment stability in intertidal mudflats: transition from biostabilization to biodestabilization - Ran Ge; Yonggang Zhao; Zheng Gong; Suna Wang; Aihong Wei; Mo Peng; Honglei Liu (Sedimentary Geology, 2025)

Effects of extracellular organic matter from bacteria on the growth, physiology, photosynthesis, and transcriptome of the bloom-forming algal species - Jiao Ran; Rong Xiang; Binghui Zheng (Journal of Hazardous Materials, 2025)

Effect of flocculant addition and organic matter content on flocculation-electroosmotic coupled dewatering of river sludge - Qing Wei; Fuyuan Ran; Suqing Wu; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Journal of Environmental Chemical Engineering, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Polypropylene microplastics reshape diazotrophic community composition and interactions in the plastisphere without affecting the rhizosphere of Capsicum annuum L. - Hongkai Liao; Tanshan Ran; Yuxin Zhao; Chunli Zheng (Science of The Total Environment, 2025)

Climate change regulated carbonate production and accumulation in the Guaymas Basin over the past ca. 450,000 years - Hong Peng; Yuchen Zheng; Meng Zhou; Yasu Wang; Lihua Ran; Han Jiang; Ligia Pérez-Cruz; Rafael Venegas; Tobias Höfig; Andreas Teske; Daniel Lizarralde; Kathleen Marsaglia; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Evaluating the effects of a pectinolytic probiotic strain as replacement of enzymatical treatments in melon juice pre-alcohol fermentation - Haoyu Niu; Xilong Zhou; Chenang Lyu; Dapeng Wang; Jian Zheng; JiYu Cheng; Ran An (International Journal of Food Microbiology, 2025)

The role and function mechanism of pilV in modulating the pathogenicity of Aeromonas hydrophila - Zhengshi Zhang; Jiayan Ran; Shengfu Zhao; Hui Luo; Shuqing Zheng; Detao Li; Ziyang Li; Yongyao Yu; Hao Xu; Ronghua Wu; Hua Ye (Aquaculture, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

Tidal influence on residual saltwater removal behind subsurface dams in unconfined coastal aquifers - Tianyuan Zheng; Ran Cao; Yunhai Fang; Jian Luo; Peihua Li; Xilai Zheng; Xiuyu Liang; Tao Liu; Marc Walther (Journal of Hydrology, 2025)

Polydopamine-functionalized metal-organic framework nanomaterials for enhanced ultrafiltration membrane performance in high-algae water treatment - Meng Yao; Yukun Li; Zhilin Ran; Ting Chen; Zheng Ju (Journal of Environmental Chemical Engineering, 2025)

Assessment of high-position glacial valleys in Southeast Tibet, China: an integrated approach using remote sensing, UAV, field investigation, and numerical simulation - Congyan Ran; Shishu Zhang; Xinfu Xing; Haizhu Qu; Zhanglei Wu; Da Zheng; Zhenhui Pan; Maohong Yao; Kai Zhang (Natural Hazards, 2025)

Analysis of tripartite evolutionary game for maritime supply chain collaboration considering carbon emission governance - Lequn Zhu; Ran Zhou; Xiaojun Li; Lin Zheng (Frontiers in Marine Science, 2025)
The maritime supply chain is undergoing a significant transformation as the industry converges on a consensus to promote low-carbon and sustainable development. In response, governments and international organizations have implemented and updated policies to establish greenhouse gas (GHG) emission targets for the shipping industry. Achieving green and low-carbon sustainable development in the maritime supply chain necessitates coordinated decision-making among three primary entities: governments, shipping companies, and port enterprises. In this paper, a combination of system dynamics (SD) and evolutionary game theory is employed to examine the decision-making behaviors of these three parties and analyze their evolutionary pathways. Data on recent investments by typical enterprises and government subsidies have been collected, and an SD model is utilized to empirically verify the overall evolutionary process of the system and conduct a sensitivity analysis. Our findings indicate that the intensity and stability of government regulatory policies are pivotal in driving the low-carbon transformation of the maritime supply chain. Notably, a nonlinear relationship is observed between the severity of government policies and enterprise decisions. Furthermore, the level of collaboration between port and shipping enterprises in selecting technological pathways directly impacts the effectiveness of emission reductions. Additionally, the extent of low-carbon preference in market demand significantly influences the effectiveness of policies and the strategic choices made by enterprises.

Bacterially mediated carbon-iron coupling drives differential effects of herbicide enantiomers on soil heavy metal bioavailability - Ran Wu; Hua Wang; Hanche Xia; Haoyi Zheng; Yaxin Zhu; Lijuan Liu; Shaoting Du (Soil Biology and Biochemistry, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Accelerating repair of infected bone defects through post-reinforced injectable hydrogel mediated antibacterial/immunoregulatory microenvironment at bone-hydrogel interface - Zheng Wang; Ying Chu; Jingyi Du; Yan Hu; Huimin Wang; Hanghang Liu; Changying Yang; Man Wang; Jiabing Ran; Aixi Yu (Carbohydrate Polymers, 2025)

Does the herbicide napropamide exhibit enantioselective effects across genus plasmid transfer from Escherichia coli to Bacillus subtilis? - Siyu Zhang; Shihao Zheng; Yanxia Gong; Yin Wang; Qing Wei; Yaxin Zhu; Lijuan Liu; Ran Wu; Shaoting Du (Journal of Hazardous Materials, 2025)

Impact of flocculant compounding on dewatering of river sludge with high water content via flocculation, filter-pressing, and electro-osmotic coupled process - Fuyuan Ran; Suqing Wu; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Journal of Environmental Chemical Engineering, 2025)

Anaerobic co-digestion of winery wastewater with sewage sludge for methane production: Complementary feedstocks and potential direct interspecies electron transfer - Zhixuan Ma; Lifang Yu; Ze Wang; Xin Tian; Lanxiang Zheng; Ran Liu (Fuel, 2025)

Ultrasonic-assisted aqueous two-phase extraction and purification of polyphenols from hawk tea (Litsea coreana var. lanuginose): Investigating its impact on starch digestion - Minze Lv; Jack Jingyuan Zheng; Lovemore Zulu; Yuhang Wang; Kayama Kayama; Ran Wei; Zhucheng Su (Food Chemistry, 2025)

Ecological risks of sulfonamides and quinolones degradation intermediates: Toxicity, microbial community, and antibiotic resistance genes - Shuo Li; Ran Wang; Yunfei Zhang; Heshan Zheng; Xu Dong; Yoong Kit Leong; Jo-Shu Chang (Bioresource Technology, 2025)

Topology optimization of bend for reducing the local resistance in a piping and duct system - Yan Tian; Ran Gao; Ruoyin Jing; Yi Wang; Angui Li; Xin Dong; Xinpeng Hao; Zheng Ji (Building and Environment, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Enhancing the efficiency of novel PCNF demulsifier for oil-contaminated wastewater treatment through numerical simulation optimization of demulsification mechanism - Meng Yao; Zheng Ju; Zhilin Ran; Ting Chen; Haifeng Pan (Journal of Water Process Engineering, 2025)

Key enzymatic activities and metabolic pathway dynamics in acidogenic fermentation of food waste: Impact of pH and organic loading rate - Yonghui Zheng; Penghui Chen; Enzhen Wang; Yuying Ren; Xueling Ran; Bowen Li; Renjie Dong; Jianbin Guo (Journal of Environmental Management, 2025)

Impact of residual antibiotics on microbial decomposition of livestock manures in Eutric Regosol: Implications for sustainable nutrient recycling and soil carbon sequestration - Linfa Fang; Prakash Lakshmanan; Xiaoxuan Su; Yujia Shi; Zheng Chen; Yu Zhang; Wei Sun; Junxi Wu; Ran Xiao; Xinping Chen (Journal of Environmental Sciences, 2025)

Low-intensity ultrasound combined with inert particles to improve denitrifying flocculated sludge performance and resulting granulation mechanism - Ran Gao; Hao Jin; Junlan Dong; Yiru Zheng; Mengru Han; Juqing Lou (Bioresource Technology, 2025)

Multiphysics simulation and optimization of the in-situ beneficiation process of ilmenite minerals from lunar regolith - Peng Zhang; Xin Liu; Guanghui Liu; Wei Dai; Hanzhe Yang; Haibo Zheng; Zhi Wang; Ran Niu; Yifan Bai; Yang Zhang; Chengbao Liu; Ge Yang; et al. (Science China Earth Sciences, 2025)

Effects of microplastics pollution in sediments on physicochemical properties and microbial community distribution in coastal Spartina alterniflora-invaded wetlands - Guo Li; Jiao Ran; Jing Dong; Kai Yang; Jingru Hu; Jing Shi; Yumiao Zhang; Jiabin Chen; Yu Zhao; Ensheng Zhu; Suzhen Huang; Zheng Zheng (Frontiers in Marine Science, 2024)
Introduction Coastal wetlands play an important role in the global ecosystem, yet they are increasingly facing ecological degradation due to pollution and the spread of invasive Spartina alterniflora (S. alterniflora) . Among the environmental challenges, microplastics (MPs) contamination in S. alterniflora -invaded coastal wetlands is of growing concern. However, the effects of MPs pollution in S. alterniflora -invaded coastal wetlands are not clear. Methods This study investigated the effects of S. altemiflora invasion on the distribution of MPs and the effects of MPs pollution on the physicochemical properties of sediments and the structure of microbial communities in the Tiaozini wetland of Jiangsu Province, China. Results and discussion The total MPs abundance of the S. altemiflora single-plant area was the highest (16.338 x10 3 items/kg d.w.). Polyurethane and Chlorinated polyisoprene are typical MPs types in the study area. Polyurethane exhibits high abundance at all sampling sites, while Chlorinated polyisoprene is one of the dominant MPs types in the single-plant and sub-mature area of S. alterniflora . The results showed that the invasion of S. alterniflora promoted the accumulation of MPs in the sediments of the coastal wetland. This accumulation increased the total organic carbon (TOC), available phosphorus (AP) and total nitrogen (TN) contents. Moreover, MPs pollution increased the ALP and SUC enzyme activities of sediment. In addition, MPs contamination increased the abundance of Proteobacteria and Bacteroidota in the sediments. This study highlights the complex interactions between MPs pollution and S. alterniflora invasion, providing the foundation for understanding the synergistic impacts of these stressors on coastal wetland ecosystems.

Transfer of pesticides and metabolites in corn: Production, processing, and livestock dietary burden - Fengjiao Hao; Xiaoqing Wang; Feixiang Ma; Ran Wang; Fengshou Dong; Xinglu Pan; Xiaohu Wu; Yongquan Zheng; Jun Xu (Science of The Total Environment, 2024)

Numerical simulation of tracer breakthrough curves in karst aquifers by a coupled discrete-continuum model - Xiaokang Zheng; Zhibing Yang; Shuangqiao Zhan; Xingwu Du; Yuncai Chen; Ran Hu; Yi-Feng Chen (Journal of Hydrology, 2024)

Spatial patterns, source apportionment, and risk assessment of polychlorinated biphenyls (PCBs) in the surface sediments of eastern China lakes along a latitudinal gradient: Insights guided by full-congener analysis - Jing Dong; Xingru Zhao; Ran Dai; Rui Guo; Chengyou Liu; Xiaoai Cui; Yaqing Liu; Hui Wang; Binghui Zheng (Journal of Hazardous Materials, 2024)

Enhanced mobilization of soil heavy metals by the enantioselective herbicide R-napropamide compared to its S-isomer: Analyses of abiotic and biotic drivers - Hua Wang; Ran Wu; Haoyi Zheng; Yanxia Gong; Yong Yang; Yaxin Zhu; Lijuan Liu; Miaozhen Cai; Shaoting Du (Journal of Hazardous Materials, 2024)

Harnessing natural light: Novel nanoheterojunction photocatalyst NaGdF4:Yb,Tm@TiO2/Cu2(OH)2CO3 for actual wastewater remediation - Mengyu Di; Wenqi Liu; Dan Shan; Yue Zhao; Changyuan Zhang; Yankun Wang; Ran Yi; Yang Wu; Jing Zheng; Baiqi Wang (Journal of Environmental Management, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

MPs and PFOS single and combined exposure significantly alter genetic expressions of growth hormone and insulin growth factor-related biomarkers during zebrafish embryonic development - Qingsong Shu; Shaolin Xie; Muhammad Junaid; Ran Zheng; Huijuan Tang; Jixing Zou; Aiguo Zhou (Science of The Total Environment, 2024)

MdAP2-like, a new regulator in apple, simultaneously modulates fruit softening and size - Miaomiao Wang; Wenduo Zhan; Ming Chen; Yanfei Guo; Hao Wang; Yao Wu; Tuanhui Bai; Jian Jiao; Chunhui Song; Jiangli Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

Enhancing Bone-Titanium integration through hydrogel coating mediated sequential M1/M2 polarization of interfacial macrophages - Zheng Wang; Honghan Yan; Man Wang; Yan Hu; Hao Zeng; Hanghang Liu; Huimin Wang; Changying Yang; Jin Liu; Aixi Yu; Jiabing Ran (Chemical Engineering Journal, 2024)

Endgroup engineering of the third component for high-efficiency ternary organic solar cells - Chanyin Cao; Xueqing Ma; Xinming Zheng; Guangliu Ran; Ziqing Bian; Yahui Liu; Wenkai Zhang; Zhishan Bo (Chemical Engineering Journal, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Simulation and experimental study on precise aeration and electric field for synergistic demulsification of emulsified oil - Meng Yao; Xiaoqing Dong; Zhilin Ran; Haifeng Pan; Ting Chen; Zheng Ju (Journal of Environmental Chemical Engineering, 2024)

Mechanism of bioactive 3,3′-diindolylmethane formation in flaxseed meal-xylose-tryptophan maillard reaction - An-Ran Zheng; Zhi-Jing Ni; Dun-Hua Liu; Ya-Jing An; Kiran Thakur; Chao-Kun Wei (Food Bioscience, 2024)

Food-grade expression and characterization of cyclomaltodextrinase from B. sphaericus E−244 in Bacillus subtilis - Ruiqi Zhou; Luhua Zheng; Bo Jiang; Weiwei He; Ran Zhang; Jingjing Chen; Assam Bin Tahir (Food Bioscience, 2024)

Green wood bio-adhesives from cellulose-derived bamboo powder hydrochars - Yong-Xing Chen; Han-Song Zhu; Fan Gao; Huan-Ran Xiong; Huan Yang; Zhi-Xiang Xu; Pei-Gao Duan; Li-Jun Zheng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Nicotinamide Riboside Promotes the Proliferation of Endogenous Neural Stem Cells to Repair Spinal Cord Injury - Jianping Zhang; Jun Shang; Han Ding; Wenxiang Li; Zonghao Li; Zhongze Yuan; Han Zheng; YongFu Lou; Zhijian Wei; Hengxing Zhou; Shiqing Feng; Xiaohong Kong; et al. (Stem Cell Reviews and Reports, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Ship Chain Navigation Co-Scheduling of Three Gorges-Gezhouba Dam under Serial-Lock Scenario - Hongwei Tian; Qianqian Zheng; Yu Zhang; Lijun He; Shun Liu; Ran Li (Journal of Marine Science and Engineering, 2024)
Motivated by the operational scenarios of lock scheduling, we propose a serial-lock chain navigation problem (SLCNP) modeled on the Three Gorges-Gezhouba Dam (TGGD) for the first time. Ship grouping, synchronized moving, and grouped waiting operations are integrated into the ship navigation process. A mixed integer programming (MIP) model that incorporates real-world constraints such as ship priority, service fairness, traffic flow equilibrium, and phased ship placement is presented to optimize ship throughput and ship stay time. To solve the SLCNP, a sort-pick strategy-based swarm intelligence algorithm (SPSSIA) framework is developed that integrates the characteristics of SLCNP through a hybrid multi-section encoding method and a two-stage heuristic decoding approach. A swarm intelligence evolution mechanism is used to improve the search ability and robustness of the framework. Several instances are generated based on real data to verify the correctness and effectiveness of the model and algorithm. Computational results demonstrate the applicability and effectiveness of the proposed SPSSIA. Further analysis of the experimental results indicates that the key impact factors significantly influence the navigational performance of the TGGD system. The results of this study will provide practical guidance for the operational processes of inland river hubs with comparable characteristics.

Effect of supercritical carbon dioxide on protein structure modification and antimicrobial peptides production of Mongolian cheese and its in vitro digestion - Yawen Geng; Yuanrong Zheng; Ran Zhou; Ming Ma (Food Research International, 2024)

Macrophage-Targeted multifunctional nanoparticles for detection and treatment of intraplaque hemorrhage - Haiyang Wang; Min Zheng; Yushi Chen; Long Cheng; Xiaotong Qi; Huilin Yu; Jianming Sun; Junjie Liu; Ruoyao Wang; Yaqin Hu; Tao Lin; Ying Zhang; et al. (Chemical Engineering Journal, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

The effect of slow-release phosphate fertilizers from digestates on maize rhizosphere soil microbial community and nutrient cycling: Response and activation mechanism - Bowen Li; Nan Zhao; Xueling Ran; Yonghui Zheng; Mostafa Sobhi; Renjie Dong; Jianbin Guo (Applied Soil Ecology, 2024)

Nrf1 Reduces COX-2 Expression and Maintains Cellular Homeostasis After Cerebral Ischemia/Reperfusion By Targeting IL-6/TNF-α Protein Production - Jing Yang; Junqing Yang; Ying Luo; Dongzhi Ran; Rongsong Xia; Qixue Zheng; Peishuang Yao; Hong Wang (Journal of Neuroimmune Pharmacology, 2024)

Assessing the impact of passenger compliance behavior in CAVs on environmental benefits - Zheng Xu; Zhe Zheng; Dong Xiao; Ran Tu; Wanjing Ma; Nan Zheng (Transportation Research Part D: Transport and Environment, 2024)

Field observations on the characteristics of sand ripples on tidal flats - Chuang Jin; Zheng Gong; Ran Ge; Xindi Chen (Sedimentary Geology, 2024)

Geochronology and Sr-Nd-Pb-Hf-O isotopes of Neoproterozoic orthogneisses in the Jiamusi Block, NE China: Implications for tectonic origin and secular crustal evolution - Xin Ding; Hao Yang; Zheng Ji; Yan-Long Zhang; Hao-Ran Wu; Yu Dong; Guan-Ying Yu; Wen-Chun Ge (Precambrian Research, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Involvement of CgHSFB1 in the regulation of self-incompatibility in ‘Shatian’ pummelo - Chenchen Liu; Xin Zheng; Jianbing Hu; Qiang Xu; Hao Wen; Zhezhong Zhang; Ran Liu; Xiangling Chen; Zongzhou Xie; Junli Ye; Xiuxin Deng; Lijun Chai (Plant Molecular Biology, 2024)

Neuroprotective and vasoprotective effects of herb pair of Zhiqiao-Danggui in ischemic stroke uncovered by LC-MS/MS-based metabolomics approach - Benxing Yao; Di Xu; Qing Wang; Lin Liu; Ziyun Hu; Wenya Liu; Qi Zheng; Huihui Meng; Ran Xiao; Qian Xu; Yudie Hu; Junsong Wang (Metabolic Brain Disease, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

ABA-importing transporter (AIT1) synergies enhances exogenous ABA minimize heavy metals accumulations in Arabidopsis - Yaxin Zhu; Yue You; Shihao Zheng; Jiaxin Li; Yuying Wang; Ran Wu; Zhiguo Fang; Huijun Liu; Shaoting Du (Journal of Hazardous Materials, 2024)

A dose-dependent effect of UV-328 on photosynthesis: Exploring light harvesting and UV-B sensing mechanisms - Yaxin Zhu; Hua Wang; Xiaobo Xiang; Kashif Hayat; Ran Wu; Jiaying Tian; Haoyi Zheng; Minghui Xie; Beier Li; Shaoting Du (Journal of Hazardous Materials, 2024)

Skillful prediction of boreal winter-spring seasonal precipitation in Southern China based on machine learning approach and dynamical ENSO prediction - Ting-wei Cao; Yi-ran Xu; Fei Zheng; Ruo-wen Yang (Theoretical and Applied Climatology, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Environmental risk mitigation of lambda-cyhalothrin using tryptophan-modified magnetic nanoparticles: A sustainable emergency response strategy - An Zhao; Linzhi Cai; Ran Li; Zhihao Zheng; Keming Jiao; Yunhao Gao (Chemical Engineering Journal, 2024)

Promotion of active H-assisted CaCO3 conversion for integrated CO2 capture and methanation - Zongze Lv; Tao Deng; Chang Gao; Yujie Zheng; Chunfei Wu; Jingyu Ran; Changlei Qin (Chemical Engineering Journal, 2024)

Spatial modelling of street-level carbon emissions with multi-source open data: A case study of Guangzhou - Yingsheng Zheng; Wenjie Li; Lu Jiang; Chao Yuan; Te Xiao; Ran Wang; Meng Cai; Haobin Hong (Urban Climate, 2024)

A review on geological storage of marine carbon dioxide: Challenges and prospects - Jinzhou Zhao; Jianchao Zheng; Lan Ren; Ran Lin; Bo Zhou (Marine and Petroleum Geology, 2024)

Experimental and numerical research on the uniaxial behavior of the stiffened circular concrete-filled steel tube stub columns - Ming Zheng; Xin Nie; Ran Ding (Engineering Structures, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Particle aggregation induced by microorganisms is a key mechanism for the biostabilization of coastal sediment - Ran Ge; Zheng Gong; Qian Feng; Suna Wang; Chuang Jin; Jiaxin Wei (Sedimentary Geology, 2024)

Dynamic changes of zinc chemical speciation and zinc-containing peptides release in oysters (Crassostrea hongkongensis) during enzymatic hydrolysis - Ran Du; Wan Li; Jiawei Li; Shan Zeng; Zhongqin Chen; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Bioscience, 2024)

Advancing immunotherapy in triple negative breast Cancer: A novel multimodal theranostic nanoplatform integrating synergetic ferroptosis and photothermal therapy - Long Cheng; Yibo Qiu; Lingyun He; Haiyang Wang; Min Zheng; Ruoyao Wang; Yaqin Hu; Huilin Yu; Wenpei Luo; Yuanyou Xia; Yang Cao; Zhigang Wang; et al. (Chemical Engineering Journal, 2024)

Distribution and transformation characteristics of water vapor field in the fissured rock mass and its ecological significance - Danhui Su; Jianwei Zhou; Haibo Feng; Ran Li; Xiaoming Zheng; Yi Zhu; Xu Han; Qingqiu Hou (Journal of Hydrology, 2024)

Metabolisms of both inorganic and methyl-mercury in hens reveal eggs as an effective bioindicator for environmental Hg pollution - Zhuhong Wang; Jing Liao; Pengxue Gai; Xiaoling Guo; Wang Zheng; Xue Li; Yulin Ran; Zhongwei Wang; Jiubin Chen (Journal of Hazardous Materials, 2024)

Synergistic effect of hydrothermal sludge and food waste in the anaerobic co-digestion process: microbial shift and dewaterability - Penghui Chen; Enzhen Wang; Yonghui Zheng; Xueling Ran; Zhengran Ren; Jianbin Guo; Renjie Dong (Environmental Science and Pollution Research, 2024)

Occurrence and dissemination of antibiotic resistance genes in the Yellow River basin: focused on family farms - Shimei Zheng; Bingjun Han; Yandong Wang; Yongzhen Ding; Ran Zhao; Fengxia Yang (Environmental Science and Pollution Research, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

Active and intelligent collagen films containing laccase-catalyzed mulberry extract and pickering emulsion for fish preservation and freshness indicator - Ruimin Ran; Yongming Xiong; Tingting Zheng; Pingping Tang; Yuanzhi Zhang; Changkai Yang; Guoying Li (Food Hydrocolloids, 2024)

Dopant-Enhanced harmonization of α-Fe2O3 oxygen migration and surface catalytic reactions during chemical looping reforming of methane - Hui-Xin Zhang; Xi-Yang Yu; Xue Su; Xin Gao; Zheng-Qing Huang; Bolun Yang; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Effect of sesbania gum on the rheological, textural, and microstructural characteristics of CaSO4-induced soy protein isolate gels - Ran Yang; Bin Yu; Laixue Ni; Yungang Cao; Qingqing Chai; Haiteng Tao; Zheng Zhang; Guimei Liu; Yunhui Cheng; Haibo Zhao; Bo Cui; Zhengzong Wu (Food Hydrocolloids, 2024)

Photocatalytic C-C coupling and H2 production with tunable selectivity based on ZnxCd1-xS solid solutions for benzyl alcohol conversions under visible light - Ran Wang; Zhiding Zheng; Zhuo Li; Xiaoxiang Xu (Chemical Engineering Journal, 2024)

A Review on Dewatering of Dredged Sediment in Water Bodies by Flocculation Processes - Qi Chen; Fuyuan Ran; Qing Wei; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan (Water, Air, & Soil Pollution, 2024)

Optimal deployment of thermal hydrolysis and anaerobic digestion to maximize net energy output based on sewage sludge characteristics - Penghui Chen; Yonghui Zheng; Enzhen Wang; Xueling Ran; Guangqun Huang; Wei Li; Renjie Dong; Jianbin Guo (Water Research, 2023)

Review: Phytate modification serves as a novel adsorption strategy for the removal of heavy metal pollution in aqueous environments - Xiaoliang Xue; Yuzhu Han; Xinming Wu; Hongji Wang; Shuang Wang; Jiaqi Zheng; Rong Ran; Chaowen Zhang (Journal of Environmental Chemical Engineering, 2023)

Effects of simultaneous CO2 addition to the fuel and oxidizer streams on soot formation in co-flow diffusion ethylene flame - Yu Yang; Shu Zheng; Yuzhen He; Hao Liu; Ran Sui; Qiang Lu (Fuel, 2023)

Identifying cadmium and lead co-accumulation from living rice blade spectrum - Shuangyin Zhang; Teng Fei; Yiyun Chen; Jiaxin Yang; Ran Qu; Jian Xu; Xiao Xiao; Xuejun Cheng; Zhongzheng Hu; Xuedong Zheng; Dengzhong Zhao (Environmental Pollution, 2023)

Enzymolysis and photothermal-mediated synergistic antimicrobial nanoplatform with programmed EPS degradation and biofilm penetration capabilities for eradication of biofilm wound infections - Dongchao Qiu; Chuchu Zheng; Youyun Zeng; Lixia Wu; Chen Huang; Ying Ran; Yiqin Ding; Jiayi Shi; Xiaojun Cai; Yihuai Pan (Chemical Engineering Journal, 2023)

Tri-modified ferric alginate gel with high regenerative properties catalysts for efficient degradation of rhodamine B - Lingxiao Zhu; Xu Zhang; Lang Ran; Heng Zhang; Yajuan Zheng; Chen Liu; Lincheng Zhou (Carbohydrate Polymers, 2023)

Livestock grazing may weaken N deposition effects on soil C:N:P stoichiometry in alpine grassland of the Qinghai-Tibetan Plateau - Hao Shen; Shikui Dong; Shuai Li; Hanzhong Zheng; Qiyun Wang; Junxiang Liu; Jiannan Xiao; Hui Zuo; Ran Zhang; Xiuchun Yang (CATENA, 2023)

A Comparative Analysis of Three Rutaceae Species Reveals the Multilayered Mechanisms of Citrus in Response to Huanglongbing Disease - Yunuo Liu; Liting Dong; Danlu Ran; Shuai Wang; Rongrong Qu; Lin Zheng; Aihong Peng; Yongrui He; Shanchun Chen; Xiuping Zou (Journal of Plant Growth Regulation, 2023)

Efficient rhodamine B dye degradation by red mud-grapefruit peel biochar catalysts activated persulfate in water - Shuman Deng; Maolin Yang; Qiang An; Zheng Li; Bin Zhao; Binbin Ran (Environmental Science and Pollution Research, 2023)

Reply to “Comment on: Traffic-related organic and inorganic air pollution and risk of development of childhood asthma: A meta-analysis” - Yunqian Chen; Yizhuo Zhao; Zheng Ran; Chang Wang; Qiong Wu; Penghui Li; Taosheng Jin (Environmental Research, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

An injectable, self-healing, and antioxidant collagen- and hyaluronic acid-based hydrogel mediated with gallic acid and dopamine for wound repair - Changkai Yang; Yuanzhi Zhang; Xiaoxia Zhang; Pingping Tang; Tingting Zheng; Ruimin Ran; Guoying Li (Carbohydrate Polymers, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Characterization of a fermented dairy, sour cream: Lipolysis and the release profile of flavor compounds - Meng-Song Wang; Min Fan; An-Ran Zheng; Chao-Kun Wei; Dun-Hua Liu; Kiran Thaku; Zhao-Jun Wei (Food Chemistry, 2023)

Impact of π–bridge unit in fully nonfused ring electron acceptor on the photovoltaic performance of organic solar cells - Wenlong Liu; Xinming Zheng; Guangliu Ran; Hao Lu; Xinjun Xu; Chuang Yao; Yahui Liu; Wenkai Zhang; Zhishan Bo (Chemical Engineering Journal, 2023)

Design of a novel chimeric peptide via dual blockade of CD47/SIRPα and PD-1/PD-L1 for cancer immunotherapy - Zheng Hu; Wanqiong Li; Shaomeng Chen; Danhong Chen; Ran Xu; Danlu Zheng; Xin Yang; Shuzhen Li; Xiuman Zhou; Xiaoshuang Niu; Youmei Xiao; Zhuoying He; et al. (Science China Life Sciences, 2023)

Enhancement of chiral drugs separation by a novel adjustable gravity mediated capillary electrophoresis combined with sulfonic propyl ether β-CD polymer - Yaqin Nan; Pingyi Zheng; Mengqi Cheng; Ran Zhao; Haijiao Jia; Qinggang Liang; Youxin Li; James J. Bao (Analytica Chimica Acta, 2023)

Hotspots and future trends of phosphorus recycling from livestock manure: A bibliometric review - Xueling Ran; Yun Deng; Naga Sai Tejaswi Uppuluri; Bowen Li; Yonghui Zheng; Penghui Chen; Renjie Dong; Joachim Müller; Jianbin Guo; Hans Oechsner (Science of The Total Environment, 2023)

Exploring the repairing mechanisms of reduced graphene oxide (rGo) on the dysregulation of Xenopus Laevis larva hypothalamus-pituitary-thyroid (HPT) axis caused by chiral triazole fungicide metconazole - Yue Deng; Meiling Zheng; Rui Liu; Haixia Zeng; Jingling Diao; Ran Xiao; Xiaoxuan Su (Pesticide Biochemistry and Physiology, 2023)

Advances in the application of metallic isotopes to the identification of contaminant sources in environmental geochemistry - Peng Wang; Jian Hu; Tingyi Liu; Jinke Liu; Shunrong Ma; Wenmin Ma; Jun Li; Houyi Zheng; Ran Lu (Journal of Hazardous Materials, 2023)

Antioxidant and antimicrobial collagen films incorporating Pickering emulsions of cinnamon essential oil for pork preservation - Ruimin Ran; Tingting Zheng; Pingping Tang; Yongming Xiong; Changkai Yang; Min Gu; Guoying Li (Food Chemistry, 2023)

Collagen films functionalized with gallic acid in the presence of laccase for beef preservation - Pingping Tang; Tingting Zheng; Ruimin Ran; Yongming Xiong; Guoying Li (Food Packaging and Shelf Life, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Deep convective clouds observed by ground-based radar over Naqu, Qinghai–Tibet Plateau - Dong Zheng; Penglei Fan; Yijun Zhang; Wen Yao; Xianggui Fang; Ran Ran (Atmospheric Research, 2023)

Increasing riverine export of dissolved organic carbon from China - Yanzi Yan; Ronny Lauerwald; Xuhui Wang; Pierre Regnier; Philippe Ciais; Lishan Ran; Yuanyi Gao; Ling Huang; Yao Zhang; Zheng Duan; Fabrice Papa; Bing Yu; et al. (Global Change Biology, 2023)
River transport of dissolved organic carbon (DOC) to the ocean is a crucial but poorly quantified regional carbon cycle component. Large uncertainties remaining on the riverine DOC export from China, as well as its trend and drivers of change, have challenged the reconciliation between atmosphere‐based and land‐based estimates of China's land carbon sink. Here, we harmonized a large database of riverine in‐situ measurements and applied a random forest model, to quantify riverine DOC fluxes (F DOC ) and DOC concentrations (C DOC ) in rivers across China. This study proposes the first DOC modeling effort capable of reproducing well the magnitude of riverine C DOC and F DOC , as well as its trends, on a monthly scale and with a much wider spatial distribution over China compared to previous studies that mainly focused on annual‐scale estimates and large rivers. Results show that over the period 2001–2015, the average C DOC was 2.25 ± 0.45 mg/L and average F DOC was 4.04 ± 1.02 Tg/year. Simultaneously, we found a significant increase in F DOC (+0.044 Tg/year 2 , p = .01), but little change in C DOC (−0.001 mg/L/year, p > .10). Although the trend in C DOC is not significant at the country scale, it is significantly increasing in the Yangtze River Basin and Huaihe River Basin (0.005 and 0.013 mg/L/year, p p = .01). Changes in hydrology, play a stronger role than direct impacts of anthropogenic activities in determining the spatio‐temporal variability of F DOC and C DOC across China. However, and in contrast with other basins, the significant increase in C DOC in the Yangtze River Basin and Huaihe River Basin is attributable to direct anthropogenic activities. Given the dominance of hydrology in driving F DOC , the increase in F DOC is likely to continue under the projected increase in river discharge over China resulting from a future wetter climate.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Kinetic modelling of the mass and heat transfer of a plant-based fishball alternative during deep-fat frying and air frying and the changes in physicochemical properties - Xinli Ran; Dingsong Lin; Lingjie Zheng; Yifan Li; Hongshun Yang (Journal of Food Engineering, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

Legacy and novel perfluoroalkyl substances in major economic species of invertebrates in South China Sea: Health implication from consumption - Jieyi Diao; Zhenwei Chen; Chuanghong Su; Jianwen Wang; Zhixin Zheng; Qiongping Sun; Lin Wang; Ran Bi; Tieyu Wang (Marine Pollution Bulletin, 2023)

Combined toxic effects of nanoplastics and norfloxacin on mussel: Leveraging biochemical parameters and gut microbiota - Ran Xu; Li'ang Li; Jiahui Zheng; Chenglong Ji; Huifeng Wu; Xiang Chen; Yuchuan Chen; Menghong Hu; Elvis Genbo Xu; Youji Wang (Science of The Total Environment, 2023)

Carbon nitride-type polymers compounded with FeOCl to enhance the catalytic removal of antibiotics over a wide pH range: Performance and mechanism - Yu Jiang; Kang Mao; Jiabing Ran; Junxia Su; Guopei Huang; Xingli Zheng; Kuankuan Zhang; Hui Guan; Changying Yang; Hua Zhang (Journal of Water Process Engineering, 2023)

Iron-mediated Reformatsky reaction of iododifluoromethyl ketones with aldehydes: Preparation of α,α-difluoro-β-hydroxyketone derivatives - Ran Sun; Xiang Lian; Jinwen Huang; Jingjing Wu; Yicong Li; Zijian Chen; Zheng Qu; Lixing Song; Fanhong Wu (Journal of Fluorine Chemistry, 2023)

Development of active packaging films based on collagen/gallic acid-grafted chitosan incorporating with ε-polylysine for pork preservation - Tingting Zheng; Pingping Tang; Changkai Yang; Ruimin Ran; Guoying Li (Food Hydrocolloids, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Particulate matter, nitrogen dioxide, and sulfur dioxide and their associations with allergic skin diseases: A systematic review and meta-analysis - Jin Huang; Wen-hao Zheng; Hong-chan Huang; Yi-guo Ran; Yi Liu; Ping Huang (Atmospheric Pollution Research, 2023)

Observed Taylor cap around a seamount intensified by a surface mesoscale eddy in the Northwest Pacific - Yansong Liu; Qiang Ren; Fei Yu; Jianfeng Wang; Ran Wang; Feng Nan; Yanan Ding; Tongtong Zheng; Chuanzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Climate Dynamics, 2023)

Effect of stress amplitude on mechanical and acoustic emission of sandstone under constant–cyclic loading - Bichuan Zhang; Yunpei Liang; Zhanyi Zhao; Quanle Zou; Haolong Zheng; Yanhao Ning; Fanjie Kong; Qican Ran (Bulletin of Engineering Geology and the Environment, 2023)

Inactivation of epithelial sodium ion channel molecules serves as effective diagnostic biomarkers in clear cell renal cell carcinoma - Qian Zheng; Yifang Wang; Ran Zhao; Peipei Han; Jun Zhao; Limei Li; Xiaohui Zhou; Ping Li; Yingxi Mo; Xinli Pan; Wenqi Luo; Xiaoying Zhou (Genes & Genomics, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Antibacterial activity and mechanism of slightly acidic electrolyzed water combined with ultraviolet light against Salmonella enteritidis - Xingyun Yuan; Yanjiao Li; Qingnan Mo; Beibei Zhang; Dengqun Shu; Lina Sun; Xianghui Zhao; Ran Zhang; Jiahui Zheng; Yingqi Jia; Yitian Zang (Food Control, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Molecular phylogenetics and population demographic history of Amphioctopus fangsiao, inferred from mitochondrial and microsatellite DNA markers - Jian Zheng; Yan Tang; Ran Xu; Xiaoying Zhang; Xiaodong Zheng (Acta Oceanologica Sinica, 2023)

Comparison of phosphorus species in livestock manure and digestate by different detection techniques - Xueling Ran; Naga Sai Tejaswi Uppuluri; Yun Deng; Yonghui Zheng; Renjie Dong; Joachim Müller; Hans Oechsner; Bowen Li; Jianbin Guo (Science of The Total Environment, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

C4 expansion of Central Asia in the middle Miocene linked to the strengthening Indian monsoon - Jian Wang; Xinying Zhou; Shiqi Wang; Hai Xu; Hermann Behling; Jie Ye; Yan Zheng; Junchi Liu; Yan Wu; Keliang Zhao; Ran Zhang; Xiaoqiang Li (Global and Planetary Change, 2023)

Improving flavor, bioactivity, and changing metabolic profiles of goji juice by selected lactic acid bacteria fermentation - Wenhui Duan; Qijie Guan; Hui-Ling Zhang; Fang-Zhou Wang; Ran Lu; De-Mao Li; Yan Geng; Zheng-Hong Xu (Food Chemistry, 2023)

Re-evaluating the accurate multiphase water distribution in coals: Unifying experiment and theory - Sijian Zheng; Yanbin Yao; Dameng Liu; Shuxun Sang; Shiqi Liu; Meng Wang; Xiaozhi Zhou; Ran Wang; Sijie Han; Tong Liu (Chemical Engineering Journal, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

Targeting autophagy receptors OPTN and SQSTM1 as a novel therapeutic strategy for osteoporosis complicated with Alzheimer's disease - Ran Duan; Chun-Gu Hong; Meng-Lu Chen; Xin Wang; Zhi-Lin Pang; Hui Xie; Zheng-Zhao Liu (Chemico-Biological Interactions, 2023)

Experimental and Numerical Studies on Bending and Failure Behaviour of Inflated Composite Fabric Membranes for Marine Applications - Yunling Ye; Jin Gan; Huabing Liu; Qingfei Guan; Zhongyi Zheng; Xiaolin Ran; Zi’ang Gao (Journal of Marine Science and Engineering, 2023)
Owing to their excellent physical characteristics of lightweightiness, compactness and rapid deployment, the inflated membrane structures satisfy the demands of maritime salvage and military transportation for long-distance delivery and rapid response. Exploring the failure behaviour of inflated membrane structures can greatly contribute to their widespread applications in ocean engineering. In this research, the main objective is to comprehensively investigate the bending and failure behaviour of inflated membrane structures. Thus, the Surface-Based Fluid Cavity method is employed to set up the finite element model (FEM) which is compared to the experimental results to verify its reliability. In parallel, the effects of internal pressure and wrinkles are discussed. An empirical expression of the ultimate bending loading was fitted by face-centred composite designs of the Response Surface Methodology. The results of experiments and FEM show that the bearing capacity of the inflated membrane structure is positively correlated with the internal pressure but decreased obviously with the occurrence and propagation of wrinkles. The deformation behaviour and the stress distribution are similar to those of the traditional four-point bending beam, and the local instability induced by wrinkles will cause structural failure. In addition, the numerical model and the proposed expression showed deviations below 5% in relation to the experimental measures. Therefore, the FEM and proposed expression are high of reliability and have important engineering guiding significance for the application of inflated membrane structures in ocean engineering.

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Engineered acetaldehyde dehydrogenase for the efficient degradation of acetaldehyde - Zheng Peng; Ran Wang; Xiaofeng Xia; Juan Zhang (Journal of Environmental Management, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

Chemical constituents from the aerial parts of Sambucus adnata Wall. and their chemotaxonomic significance - Zheng-Bo Wu; Mei-Mei Zheng; Shu-Ran Qin; Jiang-Li Huang; Dashan Li; Wen-Jing Wang (Biochemical Systematics and Ecology, 2023)

Nocardia seriolae mediates liver granulomatous chronic inflammation in Micropterus salmoides through pyroptosis - Zheng‐Yang Zhou; Shang‐Jie Bai; Chen‐Wang Lu; Bin Yang; Jun Wang; Sheng Lian; Zheng‐Ran Jian; Er‐Long Wang; Gao‐Xue Wang; Tao Liu (Journal of Fish Diseases, 2023)
Granulomatous diseases caused by Nocardia seriously endanger the health of cultured fish. These bacteria are widely distributed, but prevention and treatment methods are very limited. Chronic granulomatous inflammation is an important pathological feature of Nocardia infection. However, the molecular mechanisms of granuloma formation and chronic inflammation are still unclear. Constructing a granuloma infection model of Nocardia is the key to exploring the pathogenesis of the disease. In this study, we established a granuloma model in the liver of largemouth bass ( Micropterus salmoides ) and assessed the infection process of Nocardia seriolae at different concentrations by analysing relevant pathological features. By measuring the expression of pro‐inflammatory cytokines, transcription factors and a pyroptosis‐related protein, we revealed the close relationship between pyroptosis and chronic inflammation of granulomas. We further analysed the immunofluorescence results and the expression of pyroptosis‐related protein of macrophage infected by N. seriolae and found that N. seriolae infection induced macrophage pyroptosis in vitro. These results were proved by flow cytometry analysis of infection experiment in vivo. Our results indicated that the pyroptosis effect may be the key to inducing chronic inflammation in the fish liver and further mediating granuloma formation. In this study, we explored the molecular mechanism underlying chronic inflammation of granulomas and developed research ideas for understanding the occurrence and development of granulomatous diseases in fish.

PHB2 binds to ERβ to induce the autophagy of porcine ovarian granulosa cells through mTOR phosphorylation - Guangyu Liu; Yifan Wang; Yuxin Zheng; Jing Lv; Yuanyou Li; Ning Liu; Huimin Gao; Haohan Ran; Hong Tang; Zhongliang Jiang (Theriogenology, 2023)

Spatiotemporal variation and driving factors of water quality in Yunnan-Guizhou plateau lakes, China - Jiao Ran; Rong Xiang; Jia He; Binghui Zheng (Journal of Contaminant Hydrology, 2023)

Three-dimensional structure of mesoscale eddies and their interaction with Kuroshio based on observations from a CPIES array - Qiang Ren; Yansong Liu; Ran Wang; Feng Nan; Jianfeng Wang; Xinyuan Diao; Zifei Chen; Fei Yu; Chuangzheng Zhang; Ruixiang Zhao; Hua Zheng; Xiao-Hua Zhu (Frontiers in Marine Science, 2023)
Mesoscale eddies are widespread in the oceans; however, tracking and observing them remains a challenge. Additionally, there are few studies of eddy–Kuroshio interactions based on large-scale in situ data. Data from a large array of 39 CPIESs deployed around the Luzon Strait in 2018–2019 (12 deployed east of Taiwan within a 3 × grid) were used to reveal the three-dimensional structure of mesoscale eddies and their interaction with Kuroshio. The results show a strengthening (weakening) of the tilt of the pycnocline, which has also caused a deeper (shallower) pycnocline in eastern Taiwan following an anticyclonic (cyclonic) interaction with Kuroshio, which resulted in a strengthening (weakening) of the Kuroshio. During the anticyclonic eddy impinging Kuroshio, the downward (upward) movement at the center of the anticyclonic eddy (Kuroshio) results in a positive (negative) anomaly structure for temperature, with corresponding positive (negative) anomalies for salinity above 600 m in the intermediate layer and negative (positive) anomalies below 600 m. In contrast, when the cyclonic eddies interact with the Kuroshio, the temperature and salinity anomalies change simultaneously, with the temperature showing an overall negative anomaly and the salinity showing a negative and positive anomaly above and below 600 m, respectively. The research in this study provides the basis for further research on energy exchange during eddy–Kuroshio interactions.

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

Transcriptomics analysis reveals molecular mechanism of softening and cell wall polysaccharides-disassembling in peaches treated by flow microcirculation of sodium nitroprusside medium - Yanli Zheng; Lihua Duan; Yalin Ran; Peng Zhang; Yunbin Jiang; Zhiyong Zhao; Ziqin Li; Lan Chen; Yao Tang; Xihong Li; Xiaoyu Jia (Postharvest Biology and Technology, 2023)

Enhanced washing of cadmium and lead from polluted river sediment using horizontal electroosmosis - Ran Wen; Xiong Yang; Shuang He; Jian Wu; Hongmei Ge; Zheng Chi; Yafei Shi; Shulian Wang; Andrea R. Gerson; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

Experimental detection of two-dimensional temperature distribution in Rocket-Based Combined Cycle combustion chamber using multispectral imaging processing - Shu Zheng; Weiguang Cai; Bing Liu; Shaohua Zhu; Bo Zhou; Ran Sui; Qiang Lu (Fuel, 2023)

VELAS: An open-source toolbox for visualization and analysis of elastic anisotropy - Zheng Ran; Chunming Zou; Zunjie Wei; Hongwei Wang (Computer Physics Communications, 2023)

Efficacy and safety of granulocyte–macrophage colony-stimulating factor (GM-CSF) antibodies in COVID-19 patients: a meta-analysis - An-ran Xi; Yi-jun Luo; Jin-Tao Guan; Wei-Jie Wang; Zheng-Hao Xu (Inflammopharmacology, 2023)

Potential health and economic impacts of shifting manufacturing from China to Indonesia or India - Qi Ran; Shao-Yi Lee; Duofan Zheng; Han Chen; Shili Yang; John C. Moore; Wenjie Dong (Science of The Total Environment, 2023)

Evaluation of carbon dioxide geological sequestration potential in coal mining area - Shiqi Liu; Tong Liu; Sijian Zheng; Ran Wang; Shuxun Sang (International Journal of Greenhouse Gas Control, 2023)

Innovative natural antimicrobial natamycin incorporated titanium dioxide (nano-TiO2)/ poly (butylene adipate-co-terephthalate) (PBAT) /poly (lactic acid) (PLA) biodegradable active film (NTP@PLA) and application in grape preservation - Yanli Zheng; Xiaoyu Jia; Zhiyong Zhao; Yalin Ran; Meijun Du; Haiyu Ji; Yanfang Pan; Ziqin Li; Xiaowei Ma; Yue Liu; Lihua Duan; Xihong Li (Food Chemistry, 2023)

Effect of supercritical carbon dioxide on bacterial community, volatile profiles and quality changes during storage of Mongolian cheese - Jing Feng; Yuanrong Zheng; Xin Zhang; Ran Zhou; Ming Ma (Food Control, 2023)

Modulating coordination structures and metal environments of MOFs-Engineered electrocatalysts for water electrolysis - Huijuan Wu; Weiqiong Zheng; Ran Zhu; Mi Zhou; Xiancheng Ren; Yinghan Wang; Chong Cheng; Hongju Zhou; Sujiao Cao (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Metabolism balance regulation for squalene production by disturbing triglyceride (TAG) synthesis in Schizochytrium sp. - Ran Duan; Xueshan Pan; Keyan Li; Qinghua Yang; Xiaowen Cui; Yayun Zheng; Yinghua Lu; Chuanyi Yao; Xueping Ling (Algal Research, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

The preparation of dodecyl trimethyl ammonium bromide modified titanium dioxide for the removal of uranium - Jian Wang; Ran Ma; Zheng Jiang (Environmental Science and Pollution Research, 2022)

Genetic Differentiation Among Populations of Octopus minor Based on Simple Sequence Repeats Mined from Transcriptome Data - Ze Nan; Ran Xu; Chunqiang Hou; Xiaodong Zheng (Journal of Ocean University of China, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Neuropeptide FF-related gene in fish (Larimichthys polyactis): identification, characterization, and potential anti-inflammatory function - Ran Xiao; Zuting Guo; Li-bing Zheng; Wei Huang; Chang-feng Chi; Bao Lou (Molecular Biology Reports, 2022)

3D outcrop geologic modeling and seismic forward modeling of mound-beach complexes - Ran Xiong; Jianfeng Zheng; Xinxin Wang; Lili Huang; Liang Guo (Arabian Journal of Geosciences, 2022)

Symmetrical Sporotrichosis: Self-inoculated by Frequently Contacting Skin Lesion? - Lu Zheng; Xin Ran; Sushmita Pradhan; Yuping Ran (Mycopathologia, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

DNA Barcoding Reveals High Hidden Species Diversity of Chinese Waters in the Cephalopoda - Ran Xu; Yuhan Lü; Yan Tang; Zhiwei Chen; Chenxi Xu; Xiaoying Zhang; Xiaodong Zheng (Frontiers in Marine Science, 2022)
Species delimitation by traditional morphological methods is challenging in cephalopods due to their flexible bodies, changeable pigment traits, and sometimes high morphological homoplasy. Molecular information provides important assistance for taxonomic decision. In this study, we applied three species delimitation methods on 132 cephalopods from 7 families along Chinese waters, and we found anunderestimated species diversity in these taxa. A maximum of 56 molecular operational taxonomic units was detected, and possible cryptic diversities were revealed in Loliolus beka , Uroteuthis edulis , Octopus minor , Amphioctopus fangsiao , and Hapalochlaena lunulate . This study provides molecular evidence for the hidden species diversity along Chinese waters, and it provides insight into further taxonomic research on these morphologically variable taxa.

Characteristics of the BDS-3 multipath effect and mitigation methods using precise point positioning - Ran Lu; Wen Chen; Chenglong Zhang; Lei Li; Yu Peng; Zhengqi Zheng (GPS Solutions, 2022)

Concentration and source allocation of black carbon by AE-33 model in urban area of Shenzhen, southern China - Wenqian Chen; Xiaoyi Cao; Haofan Ran; Ting Chen; Bohan Yang; Xuan Zheng (Journal of Environmental Health Science and Engineering, 2022)

Development and validation of a transcriptomic signature-based model as the predictive, preventive, and personalized medical strategy for preterm birth within 7 days in threatened preterm labor women - Yuxin Ran; Jie He; Wei Peng; Zheng Liu; Youwen Mei; Yunqian Zhou; Nanlin Yin; Hongbo Qi (EPMA Journal, 2022)

Seepage field distribution and water inflow laws of tunnels in water-rich regions - Zheng Li; Zi-quan Chen; Chuan He; Chun-chi Ma; Chao-ran Duan (Journal of Mountain Science, 2022)

Cost Effectiveness Analysis in Short Sea Shipping: Evidence from Northeast Asian Routes - Xue-Bin Zheng; Yul-Seong Kim; Young-Ran Shin (Journal of Marine Science and Engineering, 2021)
Nowadays, roll-on/roll-off (Ro-Ro) is an important mode for short sea shipping (SSS) due to its advantages of fast and convenient load and unloading system. Despite the advantages, the market share of Ro-Ro is insignificant compared with lift-on/lift-off (Lo-Lo) in the Northeast Asian region that is geographically suitable for fostering SSS. Therefore, it is of utmost importance to have a better understanding of the effectiveness or Ro-Ro and Lo-Lo in the regional SSS market. For this purpose, this paper develops a model to estimate the total logistics cost of the two transportation modes. The total logistics costs of Ro-Ro and Lo-Lo are calculated on three major SSS routes between Korea and Japan. The results show that Lo-Lo outperforms Ro-Ro on most routes in terms of the cost effectiveness, and Ro-Ro is competitive only for high-priced and time-sensitive cargo. However, it is also documented that Ro-Ro transport has a significant impact on reduction in the total logistics costs when companies integrate the supply chain and improve the cooperative relationship to a high level.

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Fanconi anemia pathway and its relationship with cancer - Chenchen Dan; Hongjing Pei; Buzhe Zhang; Xuan Zheng; Dongmei Ran; Changzheng Du (Genome Instability & Disease, 2021)
Fanconi Anemia (FA) is a rare inherited hematological disease, caused by mutations in genes involved in the DNA interstrand crosslink (ICL) repair. Up to date, 22 genes have been identified that encode a series of functionally associated proteins that recognize ICL lesion and mediate the activation of the downstream DNA repair pathway including nucleotide excision repair, translesion synthesis, and homologous recombination. The FA pathway is strictly regulated by complex mechanisms such as ubiquitination, phosphorylation, and degradation signals that are essential for the maintenance of genome stability. Here, we summarize the discovery history and recent advances of the FA genes, and further discuss the role of FA pathway in carcinogenesis and cancer therapies.

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

Apple MdSAT1 encodes a bHLHm1 transcription factor involved in salinity and drought responses - Yu-Ying Yang; Peng-Fei Zheng; Yi-Ran Ren; Yu-Xin Yao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Planta, 2021)

Predictability of Monthly Streamflow Time Series and its Relationship with Basin Characteristics: an Empirical Study Based on the MOPEX Basins - Ran-Ran He; Yuanfang Chen; Qin Huang; Zheng-Wei Pan; Yong Liu (Water Resources Management, 2020)

Hemocytes transcriptomes reveal metabolism changes and detoxification mechanisms in response to ammonia stress in Octopus minor - Ran Xu; Xiaodong Zheng (Ecotoxicology, 2020)

Genomic sequencing and characterization of a novel group of canine bufaviruses from Henan province, China - Ran Shao; Feiyan Zheng; Siqi Cai; Jinzhao Ji; Zixin Ren; Jiawei Zhao; Liyan Wu; Jiajun Ou; Gang Lu; Shoujun Li (Archives of Virology, 2020)

The correlation analyses of bacterial community composition and spatial factors between freshwater and sediment in Poyang Lake wetland by using artificial neural network (ANN) modeling - Ran Sun; Zuxin Tu; Lin Fan; Zixia Qiao; Xiaoyan Liu; Sihai Hu; Guohua Zheng; Yaoguo Wu; Ruiwu Wang; Xiaohui Mi (Brazilian Journal of Microbiology, 2020)

Identification of proteins associated with two diverse Caulobacter phicbkvirus particles - Kiesha Wilson; Fanchao Zhu; Ran Zheng; Sixue Chen; Bert Ely (Archives of Virology, 2020)

Texture and Quality Assessment of Ready-to-eat Farmed Obscure Puffer Fish ( Takifugu obscurus ) Fillet by Evaluating Bacterial and Myofibrillar Degradation and Biochemical Changes during Refrigerated Storage - Ran Zhou; Yuanrong Zheng; Yuan Liu; Ming Ma (Journal of Aquatic Food Product Technology, 2020)

Microwave-assisted efficient synthesis of 3-substituted bis-isoxazole ether bearing 2-chloro-3-pyridyl via 1,3-dipolar cycloaddition - Ran Zheng; Fan Feng; Zhihui Zhang; Jiaxu Fu; Qing Su; Yumin Zhang; Qiang Gu (Molecular Diversity, 2020)

Terrestrial N 2 O emissions and related functional genes under climate change: A global meta‐analysis - Linfeng Li; Zhenzhen Zheng; Weijin Wang; Joel A. Biederman; Xingliang Xu; Qinwei Ran; Ruyan Qian; Cong Xu; Biao Zhang; Fang Wang; Shutong Zhou; Lizhen Cui; et al. (Global Change Biology, 2020)
Nitrous oxide (N 2 O) emissions from soil contribute to global warming and are in turn substantially affected by climate change. However, climate change impacts on N 2 O production across terrestrial ecosystems remain poorly understood. Here, we synthesized 46 published studies of N 2 O fluxes and relevant soil functional genes (SFGs, that is, archaeal amoA , bacterial amoA , nosZ , narG , nirK and nirS ) to assess their responses to increased temperature, increased or decreased precipitation amounts, and prolonged drought (no change in total precipitation but increase in precipitation intervals) in terrestrial ecosystem (i.e. grasslands, forests, shrublands, tundra and croplands). Across the data set, temperature increased N 2 O emissions by 33%. However, the effects were highly variable across biomes, with strongest temperature responses in shrublands, variable responses in forests and negative responses in tundra. The warming methods employed also influenced the effects of temperature on N 2 O emissions (most effectively induced by open‐top chambers). Whole‐day or whole‐year warming treatment significantly enhanced N 2 O emissions, but daytime, nighttime or short‐season warming did not have significant effects. Regardless of biome, treatment method and season, increased precipitation promoted N 2 O emission by an average of 55%, while decreased precipitation suppressed N 2 O emission by 31%, predominantly driven by changes in soil moisture. The effect size of precipitation changes on nirS and nosZ showed a U‐shape relationship with soil moisture; further insight into biotic mechanisms underlying N 2 O emission response to climate change remain limited by data availability, underlying a need for studies that report SFG. Our findings indicate that climate change substantially affects N 2 O emission and highlights the urgent need to incorporate this strong feedback into most climate models for convincing projection of future climate change.

Cloning and functional identification of a strigolactone receptor gene MdD14 in apple - Yu-Ying Yang; Yi-Ran Ren; Peng-Fei Zheng; Ling-Ling Zhao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Toxicity, residue, degradation and detection methods of the insecticide triazophos - Fang-Wei Yang; Yi-Xuan Li; Fa-Zheng Ren; Ran Wang; Guo-Fang Pang (Environmental Chemistry Letters, 2019)

Automated Detection of Vulnerable Plaque for Intravascular Optical Coherence Tomography Images - Ran Liu; Yanzhen Zhang; Yangting Zheng; Yaqiong Liu; Yang Zhao; Lin Yi (Cardiovascular Engineering and Technology, 2019)

Seasonal variation in the groundwater dependency of two dominant woody species in a desert region of Central Asia - Xue Wu; Xin-Jun Zheng; Xin-Wei Yin; Yue-Meng Yue; Ran Liu; Gui-Qing Xu; Yan Li (Plant and Soil, 2019)

NIS and epithelial-mesenchymal transition marker expression of circulating tumor cells for predicting and monitoring the radioactive iodine-131 therapy effect in differentiated thyroid cancers - Lei Zheng; Guiyu Wang; Wei Guo; Deng Pan; Laiping Xie; Song He; Chaoxue Luo; Hongmin Li; Yaling Ran; Shiyang Wu; Fang Liu; Xiaoli Zhang; et al. (Molecular Biology Reports, 2019)

Elbow Malformation with Osteoarthritis and Bone Destruction Caused by Chromoblastomycosis - Lu Zheng; Xin Ran; Yaling Dai; Yuping Ran (Mycopathologia, 2019)

Characterizing groundwater flow in a translational rock landslide of southwestern China - Hongbin Lv; Chengpeng Ling; Bill X. Hu; Jiaxin Ran; Yanan Zheng; Qiang Xu; Juxiu Tong (Bulletin of Engineering Geology and the Environment, 2019)

In-depth analysis of the genome of Trypanosoma evansi, an etiologic agent of surra - Lili Zheng; Ning Jiang; Xiaoyu Sang; Naiwen Zhang; Kai Zhang; Hongyu Chen; Na Yang; Ying Feng; Ran Chen; Xun Suo; Qijun Chen (Science China Life Sciences, 2019)

Old method not old-fashioned: parallelism between wing venation and wing-pad tracheation of cockroaches and a revision of terminology - Xin-Ran Li; Yu-Hong Zheng; Chen-Chen Wang; Zong-Qing Wang (Zoomorphology, 2018)

Correction to: Analysis of the complete genomic sequence of a novel virus, areca palm necrotic spindle-spot virus, reveals the existence of a new genus in the family Potyviridae - Ke Yang; Minyuan Ran; Zengping Li; Meijiao Hu; Li Zheng; Wenbo Liu; Pengfei Jin; Weiguo Miao; Peng Zhou; Wentao Shen; Hongguang Cui (Archives of Virology, 2018)

Analysis of the complete genomic sequence of a novel virus, areca palm necrotic spindle-spot virus, reveals the existence of a new genus in the family Potyviridae - Ke Yang; Minyuan Ran; Zengping Li; Meijiao Hu; Li Zheng; Wenbo Liu; Pengfei Jin; Weiguo Miao; Peng Zhou; Wentao Shen; Hongguang Cui (Archives of Virology, 2018)

Perfluoroalkyl Substances in Water from the Yangtze River and Its Tributaries at the Dividing Point Between the Middle and Lower Reaches - Ke-Yan Tan; Guo-Hui Lu; Xin Yuan; Yu Zheng; Peng-Wei Shao; Jing-Yi Cai; Yi-Ran Zhao; Xiao-Hua Zhu; Yong-Liang Yang (Bulletin of Environmental Contamination and Toxicology, 2018)

Effects of wind–wave disturbances on adsorption and desorption of tetracycline and sulfadimidine in water–sediment systems - Qianjiahua Liao; Zheng Huang; Shu Li; Yi Wang; Yuqing Liu; Ran Luo; Jingge Shang (Environmental Science and Pollution Research, 2018)

The effect of concurrent hand movement on estimated time to contact in a prediction motion task - Ran Zheng; Brian K. V. Maraj (Experimental Brain Research, 2018)

A divergent lineage among Octopus minor (Sasaki, 1920) populations in the Northwest Pacific supported by DNA barcoding - Ran Xu; Qikang Bo; Xiaodong Zheng (Marine Biology Research, 2018)

Association of ulcerative colitis with transcobalamin II gene polymorphisms and serum homocysteine, vitamin B12, and folate levels in Chinese patients - Shuzi Zheng; Wei Yang; Chaoqun Wu; Liang Sun; Daopo Lin; Xiuqing Lin; Lijia Jiang; Ran Ding; Yi Jiang (Immunogenetics, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Legacy effects of simulated short-term climate change on ammonia oxidisers, denitrifiers, and nitrous oxide emissions in an acid soil - Xiaoya Xu; Xiaorui Liu; Yong Li; Yu Ran; Yapeng Liu; Qichun Zhang; Zheng Li; Yan He; Jianming Xu; Hongjie Di (Environmental Science and Pollution Research, 2017)

Characterization of Collagen Enzymatic Hydrolysates Derived from Lizardfish ( Synodus fuscus ) Scales - Junde Chen; Ying Liu; Ruizao Yi; Long Li; Ran Gao; Nuohua Xu; Meihua Zheng (Journal of Aquatic Food Product Technology, 2017)

Warmer and drier conditions and nitrogen fertilizer application altered methanotroph abundance and methane emissions in a vegetable soil - Yu Ran; Jianli Xie; Xiaoya Xu; Yong Li; Yapeng Liu; Qichun Zhang; Zheng Li; Jianming Xu; Hongjie Di (Environmental Science and Pollution Research, 2017)

Performance and microbial community structures of hydrolysis acidification process treating azo and anthraquinone dyes in different stages - Na Liu; Xuehui Xie; Bo Yang; Qingyun Zhang; Chengzhi Yu; Xiulin Zheng; Leyi Xu; Ran Li; Jianshe Liu (Environmental Science and Pollution Research, 2017)

A new sesquiterpene from the gorgonian coral Menella sp. - Qi Peng; Fen Liu; Huan Sun; Xiao-Jian Liao; Mei-Ran Feng; Ting-Ting Liu; Zheng-Xiong Xu; Jun Zhang; Shi-Hai Xu (Natural Product Research, 2016)

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Simultaneous optimization of evacuation route and departure time based on link-congestion mitigation - Zhengfeng Huang; Pengjun Zheng; Gang Ren; Yang Cheng; Bin Ran (Natural Hazards, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Evaluation of Groundwater Leakage into a Drainage Tunnel in Jinping-I Arch Dam Foundation in Southwestern China: A Case Study - Yi-Feng Chen; Jia-Min Hong; Hua-Kang Zheng; Yi Li; Ran Hu; Chuang-Bing Zhou (Rock Mechanics and Rock Engineering, 2016)

Temporal and spatial distributions of sodium and polyamines regulated by brassinosteroids in enhancing tomato salt resistance - Qingsong Zheng; Jinlong Liu; Ran Liu; Hao Wu; Chaoqiang Jiang; Changhai Wang; Yongxiang Guan (Plant and Soil, 2016)

Variability in the composition and export of silica in the Huanghe River Basin - XiangBin Ran; Hong Che; JiaYe Zang; YongGui Yu; Sen Liu; LiLi Zheng (Science China Earth Sciences, 2015)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

Landslides triggered by the 20 April 2013 Lushan, China, Mw 6.6 earthquake from field investigations and preliminary analyses - Chong Xu; Xiwei Xu; J. Bruce H. Shyu; Mingxing Gao; Xibin Tan; Yongkang Ran; Wenjun Zheng (Landslides, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

Acute systemic accumulation of acrolein in mice by inhalation at a concentration similar to that in cigarette smoke - Melissa Tully; Lingxing Zheng; Glen Acosta; Ran Tian; Riyi Shi (Neuroscience Bulletin, 2014)

Inter-annual variations in vegetation and their response to climatic factors in the upper catchments of the Yellow River from 2000 to 2010 - Ran Cao; Weiguo Jiang; Lihua Yuan; Wenjie Wang; Zhongliang Lv; Zheng Chen (Journal of Geographical Sciences, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Ultrasound-Microbubble Transplantation of Bone Marrow Stromal Cells Improves Neurological Function after Forebrain Ischemia in Adult Mice - Zili Gong; Hong Ran; Shengzheng Wu; Jie Zhu; Jian Zheng (Cell Biochemistry and Biophysics, 2014)

Research on the critical conditions for clay particle release during saline aquifer freshening process - Xilai Zheng; Ran Chen (Journal of Ocean University of China, 2014)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Polycyclic aromatic hydrocarbons (PAHs) in rural soils of Dongjiang River Basin: occurrence, source apportionment, and potential human health risk - Taihui Zheng; Yong Ran; Laiguo Chen (Journal of Soils and Sediments, 2014)

Incubation of sperm heads impairs fertilization and early embryo development following intracytoplasmic sperm injection (ICSI) by decreasing oocyte activation in mice - Hui Long; Sheng-Sheng Lu; Yan-Ping Kuang; Zhi-Guang Yan; Hong-Xing Liang; Sha Yu; Wei-Ran Chai; Zheng Yan; Qi-Feng Lyu (Biotechnology Letters, 2013)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Adaptive Genetic Algorithm for Daily Optimal Operation of Cascade Reservoirs and its Improvement Strategy - Kan Yang; Jiao Zheng; Min Yang; Ran Zhou; Guoshuai Liu (Water Resources Management, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

Erratum to: Recombinant HCMV UL128 expression and functional identification of PBMC-attracting activity in vitro - Huihui Gao; Ran Tao; Qi Zheng; Jun Xu; Shiqiang Shang (Archives of Virology, 2013)

Recombinant HCMV UL128 expression and functional identification of PBMC-attracting activity in vitro - Gao Hui-hui; Tao Ran; Zheng Qi; Xu Jun; Shang Shi-qiang (Archives of Virology, 2013)

Different effects of omega-3 fatty acids on the cell cycle in C2C12 myoblast proliferation - Yunqian Peng; Yu Zheng; Yunsheng Zhang; Jie Zhao; Fei Chang; Tianyu Lu; Ran Zhang; Qiuyan Li; Xiaoxiang Hu; Ning Li (Molecular and Cellular Biochemistry, 2012)

High-level expression of bioactive recombinant human lysozyme in the milk of transgenic mice using a modified human lactoferrin BAC - Shen Liu; Xiangqing Li; Dan Lu; Shengzhe Shang; Meili Wang; Min Zheng; Ran Zhang; Bo Tang; Qiuyan Li; Yunping Dai; Ning Li (Transgenic Research, 2012)

Human Pathogenic Fungi in China—Emerging Trends from Ongoing National Survey for 1986, 1996, and 2006 - S. X. Wu; N. R. Guo; X. F. Li; W. Q. Liao; M. Chen; Q. Q. Zhang; C. Y. Li; R. Y. Li; G. S. Bulmer; D. M. Li; L. Y. Xi; S. Lu; et al. (Mycopathologia, 2011)

Effects of the Metals Lead and Zinc on the Growth, Development, and Reproduction of Pardosa Astrigera (Araneae: Lycosidae) - Xiao-qiong Chen; Zheng-tian Zhang; Ran Liu; Xiu-Ling Zhang; Jian Chen; Yu Peng (Bulletin of Environmental Contamination and Toxicology, 2011)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Functional recombinant human anti-HAV antibody expressed in milk of transgenic mice - Ran Zhang; Man Rao; Chuan Li; Jingyuan Cao; Qinglin Meng; Min Zheng; Meili Wang; Yunping Dai; Mifang Liang; Ning Li (Transgenic Research, 2009)

Construction of the Vero cell culture system that can produce infectious HCV particles - Jia Guo; Ran Yan; Guodong Xu; Weiyun Li; Congyi Zheng (Molecular Biology Reports, 2009)

Iron contributes to the formation of catechol isoquinolines and oxidative toxicity induced by overdose dopamine in dopaminergic SH-SY5Y cells - Ran Wang; Hong Qing; Xiao-Qian Liu; Xiao-Lin Zheng; Yu-Lin Deng (Neuroscience Bulletin, 2008)

Study on the Interaction between Florasulam and Bovine Serum Albumin - Dehuan Ran; Xia Wu; Jinhua Zheng; Jinghe Yang; Haiping Zhou; Meifeng Zhang; Yongjun Tang (Journal of Fluorescence, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)